EFISIENSI TEKNIS USAHATANI JAGUNG DI DESA SUKA PINDAH - Utama, Satria Putra (Jurnal AGRISEP, 2004)
The general  objective  of the study  was to estimate  technical  efficiency  of farmers  under Bengkulu Regional Development Project (BRDP) through Unit Pengelola Keuangan Desa (UPKD) of com farmers'  practice  in Suka Pindah,  Lubuk Pinang  Sub-district,  Bengkulu  Province.   Suka Pindah was choosen  by purposive  method  because  this  area one of the production  center  for com in Bengkulu Province.  The research  was conducted  on December  2003, using a total of 30 respondents  chosen by simple random  sampling  from  138 farmers.   The stochastic  frontier production  function estimation using MLE showed that seed and labour had positive significant  influence  on the value of the output. Nitrogen  (urea)   coefficient  had negative  sign but this was not Significant.  SP36, KGf, Herbidde  and UPKD had positive sign, but these were not significant.   The average of technical efficiency  was 70 % for the com  farmers'in   Suka Pindah, it's mean that there is chance to increase  the effiCiency around 30 % more compare to the best farmers' practices.